Body Image and Sexual Dissatisfaction: Differences Among Heterosexual, Bisexual, and Lesbian Women - Moreno-Domínguez, Silvia; Raposo, Tania; Elipe, Paz (Frontiers in Psychology, 2019)
Gender-based differences in body image dissatisfaction are not conclusive. Women’s body experiences and their impact on sexual satisfaction may advance knowledge on how heterosexual, bisexual, and lesbian women internalize heterosexist values. In this study, we quantitatively examined the degree of body image and sexual dissatisfaction experienced by heterosexual, bisexual, and lesbian women, to determine whether body dissatisfaction can predict sexual dissatisfaction. Three hundred and fifty-four women completed an online survey measuring body and sexual dissatisfaction. No sexual orientation-based differences were observed in body or sexual dissatisfaction; however, body concerns were found to have less influence on sexual dissatisfaction in lesbian women compared to heterosexual and bisexual women. Standards of beauty remain constant among all women, yet removing themselves from the male gaze may be interpreted as a protective factor which shields women from expressing concern about their appearance during sexual activity.